The Impact of Supply Chain Dynamic Evaluation of Economic Stability of Enterprises of Radio-electronic Complex in Russia - T. A Burtseva; K. A Kushnir; A. A Kuznetsova; K. V Naydyonkova (International Journal of Supply Chain Management, 2020)
Abstract- This research aims to assess the impact of supply chain capacity on competitiveness and business efficiency of enterprises of radio-electronic complex in Russia. The aim of the scientific article is to approve the results of quantitative measuring of an economic stability of enterprises of radio-electronic cluster in Russia that let diagnose problems of their development. The methodological basis of the research is a general and statistical method of dynamic standard, index and coefficient analysis, method of paired comparisons, methods of evaluation a financial stability of enterprises. The results of the research: factors, economic profile and normative and evaluative model of economic stability of enterprises are offered.